The Pallbearer E3 ligase promotes actin remodeling via RAC in efferocytosis by degrading the ribosomal protein S6. - Xiao, H.; Wang, H.; Silva, E.A.; Thompson, J.; Guillou, A.; Yates, J.R.; Buchon, N.; Franc, N.C. (Developmental Cell, 2015)
Clearance of apoptotic cells (efferocytosis) is achieved through phagocytosis by professional or amateur phagocytes. It is critical for tissue homeostasis and remodeling in all animals. Failure in this process can contribute to the development of inflammatory autoimmune or neurodegenerative diseases. We found previously that the PALL-SCF E3-ubiquitin ligase complex promotes apoptotic cell clearance, but it remained unclear how it did so. Here we show that the F-box protein PALL interacts with phosphorylated ribosomal protein S6 (RpS6) to promote its ubiquitylation and proteasomal degradation. This leads to RAC2 GTPase upregulation and activation and F-actin remodeling that promotes efferocytosis. We further show that the specific role of PALL in efferocytosis is driven by its apoptotic cell-induced nuclear export. Finding a role for RpS6 in the negative regulation of efferocytosis provides the opportunity to develop new strategies to regulate this process.